(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Pluralismo religioso e luoghi di culto - 2. Gli edifici di culto nell’ordinamento italiano - 2.1. La normativa unilaterale statale: una tutela plurifunzionale - 2.2. La normativa pattizia, tra garanzia e promozione degli interessi religiosi - 2.3. La legislazione urbanistica e antisismica - 2.4. Apertura e finanziamento degli edifici di culto - 3. I luoghi di culto delle confessioni religiose prive di intesa - 4. La questione dei luoghi di culto islamici - 5. Osservazioni conclusive. Religious freedom and places of worship in Italian Law ABSTRACT: This paper deals with the complex legal framework and major issues concerning the churches and other places of worship in Italian legislation, which aims to protect an extraordinary historical and artistic heritage but, in the same time, is marked by an increasing inadequacy in order to meet the needs of new religious communities.